Extraction Methods Determine the Quality of Soil Microbiota Acquisition - Zhuoxin Liu; Chi Zhang; Jiejia Ma; Qianze Peng; Xiaohua Du; Shu’e Sun; Ju’e Cheng; Weiye Peng; Lijie Chen; Zepei Gu; Weixing Zhang; Pin Su; et al. (Microorganisms, 2024)
The soil microbiome plays a key role in plant health. Native soil microbiome inoculation, metagenomic profiling, and high-throughput cultivation require efficient microbe extraction. Sonication and oscillation are the most common methods used to extract soil microbiomes. However, the extraction efficiency of these methods has not been investigated in full. In this study, we compared the culturable microbe numbers, community structures, and alpha diversities among the different methods, including sonication, oscillation, and centrifugation, and their processing times. The study results showed that sonication significantly increases the culturable colony number compared with oscillation and centrifugation. Furthermore, the sonication strategy was found to be the main factor influencing extraction efficiency, but increased sonication time can aid in recovery from this impact. Finally, the extraction processing times were found to have a significant negative relationship with α-diversity among the extracted microbiota. In conclusion, sonication is the main factor for enriching in situ microbiota, and increased extraction time significantly decreases the α-diversity of the extracted microbiota. The results of this study provide insights into the isolation and utilization of different microorganism sources.